Gastrointestinal Basidiobolomycosis: An Emerging Disease Mimicking Obstructing Colon Cancer, Case Report - Awadh, Amal; Hadi, Sara; Safar, Omar; AlGhusadi, Huda; Yassin, Maha; Alhazmi, Ahmad; AlShehri, Ali (International Journal of Innovative Research in Medical Science, 2024)
Gastrointestinal obstruction is a common scenario that is seen on daily basis at hospitals having a general surgery service we are discussing a rare case of gastrointestinal Basidiobolomycosis that mimicking a presentation of obstructing colon cancer.